2020
DOI: 10.33620/fc.2173-9218.(2020/vol12).003.05
|View full text |Cite
|
Sign up to set email alerts
|

Farmacia comunitaria, adherencia al tratamiento y COVID-19

Abstract: La falta de adherencia es un problema mundial cada vez mayor y es la responsable de que los resultados esperados en salud se alejen de la realidad, aumentando el gasto sanitario. Comprender por qué un paciente no es adherente requiere identificar los factores implicados en su caso concreto y personalizar las estrategias a seguir. Para abordar la no adherencia desde la farmacia comunitaria tenemos el protocolo de la guía ADHe+ de dispensación y uso racional del medicamento, que clasifica a los pacientes no adhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 7 publications
0
3
0
1
Order By: Relevance
“…In our Sleeved arm-1: arm covered with a single-layer cotton shirt sleeve, 1 mm; Sleeved arm-2: arm covered with two layers sleeve containing a cotton shirt and a polar fabric sweater, country, it is mainly the nursing staff who monitor hypertensive patients [6]. At present, coordination mechanisms are already in place between different levels of care (Primary Care Center, Hospital and Pharmacy Offices) [7].…”
Section: Importance Of Knowledge Perception and Practice Of Health Pr...mentioning
confidence: 99%
See 1 more Smart Citation
“…In our Sleeved arm-1: arm covered with a single-layer cotton shirt sleeve, 1 mm; Sleeved arm-2: arm covered with two layers sleeve containing a cotton shirt and a polar fabric sweater, country, it is mainly the nursing staff who monitor hypertensive patients [6]. At present, coordination mechanisms are already in place between different levels of care (Primary Care Center, Hospital and Pharmacy Offices) [7].…”
Section: Importance Of Knowledge Perception and Practice Of Health Pr...mentioning
confidence: 99%
“…In our country, it is mainly the nursing staff who monitor hypertensive patients [6]. At present, coordination mechanisms are already in place between different levels of care (Primary Care Center, Hospital and Pharmacy Offices) [7].…”
mentioning
confidence: 99%
“…Si bien la adherencia ya era un tema de complejidad e interés en salud pública, la COVID-19 genera nuevos desafíos por ser una situación novedosa, inesperada, de difícil control por la forma en la que se propaga, marcada por incertidumbres y evidencias científicas en construcción que, incluso, en algunos casos es contradictoria por parte de las instancias encargadas de ofrecer información veraz, o por parte de otros sectores (por ejemplo, redes) que contribuyen a la propagación de una información incorrecta. Por tanto, realizar un abordaje de la adherencia en este contexto exige urgentemente el trabajo multidisciplinar y conjunto entre las instancias gubernamentales, el personal de la salud, el paciente y el entorno (García-Zaragozá et al, 2020).…”
Section: Palabras Claveunclassified
“…Pharmacies. It has been shown that telemedicine can enhance and optimize the work of community and hospital pharmacies [112][113][114][115]. It was demonstrated that telemedicine services provided after-hours by pharmacists in three community hospitals without 24-hour pharmacy services led to the improvement of drug safety since prescribing accuracy was verified [116,117].…”
Section: Virtual Clinical Trialsmentioning
confidence: 99%